(untitled) (Veterinary Science, 2017)
The wall structures of Mycobacteria are usually associated with the ability to form biofilm and motility by sliding. This study was performed with three strain of Environmental Mycobacteria (MA): Mycobacterium smegmatis, Mycobacterium gordonae and Mycobacterium porcinum. The goals of this paper were: a) to establish by MALDI-TOF mass spectrometry (MS) whether there are differences in the lipid carbon chain composition in the cell wall when they are in planktonic growth or forming biofilm; b) to evaluate the relation between lipid carbon chain composition and their sliding and biofilm formation ability. M. porcinum and M. smegmatis formed biofilms of different sizes and presented motility. M. gordonae developed poor biofilm and did not move. MALDI-TOF spectra obtained from EM in a planktonic state differ from EM biofilm–grown ones in their cell–wall lipidic carbon chain composition. EM biofilm–grown spectra show a greater diversity. All biofilm–grown EM spectra present short chain mycolic acids. These results suggest the importance of these mycolic acids in the formation of biofilm, especially in its maturation. M. gordonae presented also a higher proportion of long-chain fatty acid, compared to M. smegmatis and M. porcinum. The presence of long hydrophobic chains could possibly generate a greater friction, thus reducing its motility.